(untitled) - Mader, Sylvia S. (Boston, 2005)
Renowned for her effective learning systems, respected author Sylvia Mader has helped thousands of entry-level students understand and enjoy the principles of human anatomy and physiology. Mader expertly weaves up-to-date informative content with effective learning systems, piecing together the facts and fascination of human anatomy and physiology. With the fifth edition of Understanding Human Anatomy and Physiology, your introductory, one-semester students have the opportunity to experience an effective blend of up-to-date, informational content with several new features and an extensively enhanced multimedia support system.
Keywords: Sinh lý con người,Giải phẫu người,Human physiology,Human anatomy